Hydrodynamic angles, orientation and velocity of the hand in front crawl swimming - Samson, M.; Monnet, T.; Bernard, A.; Lacouture, P.; David, L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The hydrodynamic parameters of the hand (angle of attack, sweepback, velocity and orientation) play an important role in the generation of the resultant forces. These parameters were measured throughout an aquatic stroke to study the possible modifications caused by a variation of the swimming pace. Seventeen competitive swimmers swam at the long distance, middle distance and sprint paces. Parameters were calculated from the trajectory of seven markers on the hand measured with an optoelectronic system. Results showed that sweepback and angle of attack, and orientation of the hand do not vary significantly depending to the pace. Only the velocity of the hand increases when the pace increases, but only during the less propulsive phases. The increase of pace is then explained by the swimmer's capacity to maintain propulsive phases rather than increasing the force generation within each cycle.